PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS BERPENGARUH TERHADAP BELANJA MODAL PEMERINTAH - Kanaiya, I Putu Chio; Mustanda, I Ketut (E-Jurnal Manajemen; Vol 9 No 3 (2020)DO - 10.24843/EJMUNUD.2020.v09.i03.p15, 2020)
Capital expenditure is component of direct expenditure on government budget that produces fixed assets. In utilizing the resulting fixed assets, in direct contact with public services or are used by the community and some are not directly utilized by the public. Capital expenditure allocation is based on regional own-source revenue, transfers from the central government in the form of general allocation funds and special allocation funds. This study aims to determine the significance of the effect of regional own-source revenue, general allocation funds and special allocation funds for local government capital expenditure in Bali. The sampling method used is saturation sampling. The data collection uses the observation method in the financial data during 2014 - 2018 with multiple linear regression. Local own revenues and special allocation funds have positive and significant impact on capital expenditure. General allocation funds have negative and significant impact on capital expenditure. Keywords: regional own-source revenue, general allocation fund, special allocation fund,                capital expenditure.